PROFITABILITAS , UKURAN PERUSAHAAN DAN PENGARUHNYA TERHADAP STRUKTUR MODAL - EFI TAJUROH AFIAH; YUSSI - (STIE Indonesia Malang, 2019)
This research aims to examine the effect of Profitability, Company Size on Capital Structure . The method used in this research is associative research method with quantitative approach. The sample in this study was obtained by purposive sampling method. Based on the existing criteria, there were 9 companies that became the research sample. The analysis technique used is multiple linear regression. The results of analysis show that profitability has a negative and significant effect on Capital Structure. Company size does not have a significant effect on Capital StructureKeywords: Capital Structure, Profitability, Company Size.